Developmental riboflavin deficiency results in structural and functional changes in the neural retina and RPE - Xue Zhao; Mustafa S. Makia; Muna I. Naash; Muayyad R. Al-Ubaidi (Redox Biology)
The retina, a metabolically active tissue, relies on adequate flavin levels for optimal function. Our previous research demonstrated that ablation of RTBDN, a retina-specific riboflavin binding protein, plays a pivotal role in maintaining flavin levels, leading to progressive retinal degeneration. This raises the fundamental question of how riboflavin deficiency impacts retinal structure and function. We have previously evaluated an adult diet-induced model of riboflavin deficiency and showed that lack of flavins resulted in severe functional and structural deficits in the neural retina and retinal pigment epithelium with increased oxidative stress and metabolic dysregulation. Ariboflavinosis resulting from mutations in riboflavin transporters manifests early in life and is treatable with riboflavin supplementation. To mimic ariboflavinosis, we established an early-onset dietary model. At postnatal day 30, we observed a pronounced retinal phenotype characterized by early decline in cone function and subsequent loss of cone photoreceptors, while rods remained unaffected. Notably, RTBDN exhibited a biphasic response to early ariboflavinosis: initially upregulated, suggesting a protective role in maintaining retinal flavin levels, but decreased as deficiency persisted with subsequent photoreceptor functional decline. Riboflavin supplementation partially ameliorated these phenotypes by restoring retinal flavin and RTBDN levels, resulting in improvements in retinal structure and function. However, some cellular changes in the RPE remained irreversible and cone count was not restored. These findings underscore the critical roles of riboflavin and RTBDN in maintaining retinal and RPE health and highlight the importance of early detection and intervention for optimal therapeutic outcomes.